Manajemen Kurikulum dalam Mengembangkan Kecerdasan Spiritual Anak di PAUD Islam Terpadu Rumah Lebah Tabalong - Sri Hartini Astuti; Husnul Khotimah (STIT Syekh Muhammad Nafis Tabalong, 2025)
Education in early childhood is a crucial phase in life which is often referred to as the golden age. During this period, children experience accelerated development in various aspects, such as physical, motor, intellectual, social-emotional, as well as language and communication skills. In addition, spiritual intelligence has an important role in shaping children's character and moral values from an early age, guiding them to become ethical and religious individuals. The integration between IQ and EQ will run more optimally if it is supported by spiritual intelligence. The cultivation of spiritual values cannot be separated from the role of the curriculum as the main component in the educational process. This research aims to find out how curriculum management develops children's spiritual intelligence. This research was conducted using field research methods with a qualitative approach. The findings show that effective curriculum management allows the learning process to run comprehensively, planned, and in accordance with the stages of child development, thereby encouraging balanced growth between intellectual, emotional, and spiritual intelligence. A curriculum that is integrated with religious and moral values can help children live and apply spiritual values in their daily lives.